A guide to the World Anti-Doping Code : a fight for the spirit of sport - David, Paul (Cambridge University Press, 2008)
Doping is the biggest problem facing sport. The World Anti-Doping Code has been adopted by sporting organisations worldwide at both national and international level to provide a consistent and harmonised approach to anti-doping measures. The adoption of the Code, and its interpretation and application by the Court of Arbitration for Sport, has brought about great changes in sports law. This book provides a guide to the Code, illustrated through summaries of decisions by the Court of Arbitration for Sport and national level tribunals which show the Code in operation. It will assist all those involved in sport, whether as administrators, coaches or players, together with those who advise in the area and those interested in the operation of the current anti-doping regime. The book also explains the Amendments to the Code agreed in 2007 which are scheduled to come into force by January 2009.
Keywords: World Anti-Doping Agency : World Anti-Doping Code; World Anti-Doping Agency; Doping in sports : Law and legislation